Inflammatory bowel disease-associated Escherichia coli strain LF82 in the damage of gut and cognition of honeybees - Chang, Ruqi; Chen, Jieteng; Zhong, Zhaopeng; Li, Yiyuan; Wu, Kaichun; Zheng, Hao; Yang, Yunsheng (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with inflammatory bowel disease (IBD) are often accompanied with some cognitive impairment, but the mechanism is unclear. By orally exposing honeybees (Apis mellifera) to IBD-associated Escherichia coli LF82 (LF82), and non-pathogenic Escherichia coli MG1655 (MG1655) as the normal strain, we investigated whether and how LF82 induces enteritis-like manifestations and cognitive behavioral modifications in honeybees using multiparametric analysis. LF82 significantly increased gut permeability, impaired learning and memory ability in olfactory proboscis extension response conditioning, and shortened the lifespan of honeybees. Compared to MG1655, LF82 reduced the levels of tryptophan metabolism pathway substances in the honeybee gut. LF82 also upregulated genes involved in immune and apoptosis-related pathways and downregulated genes involved in G protein-coupled receptors in the honeybee brain. In conclusion, LF82 can induce enteritis-like manifestations and cognition impairment through gut metabolites and brain transcriptome alteration in honeybees. Honeybees can serve as a novel potential model to study the microbiota-gut-brain interaction in IBD condition.